The ‘dark matter’ of ubiquitin-mediated processes: using multiple approaches to investigate ubiquitin recognition - Radley, Elizabeth H. (2020)
Post-translational ubiquitin modification of target proteins acts to regulate a diverse range of cellular processes, many of which are biomedically relevant. To allow this diversity ubiquitin modifications exhibit remarkable complexity, determined by a combination of polyubiquitin chain length, linkage type, numbers of ubiquitin chains per target, and decoration of ubiquitin with other small modifiers. This ubiquitination complexity is interpreted through selective recognition by ubiquitin-binding domains (UBDs). However, there is a notable mismatch between the number of ubiquitin-mediated processes, specific (poly)ubiquitin signal variations, and functionally-verified endogenous UBDs. This led to the hypothesis that many endogenous UBDs have been overlooked and that there exist additional layers to specific ubiquitin recognition yet to be discovered. To test this hypothesis three main approaches are presented; bioinformatic review and analysis, high throughput Phage Display, and biochemical (proteomic) approaches, towards the identification of previously overlooked UBDs. Firstly, a comprehensive bioinformatic overview of the variety of UBDs and their classifications was conducted resulting in up to date, human specific and, where possible, functionally-verified SLiMs for the identification of new UBDs. Secondly, Phage Display was used to pan a randomised peptide library against wildtype-, phosphomimetic- and phosphoubiquitin with Next-Generation Sequencing (NGS) employed to suggest novel artificial ubiquitin-binding peptides. Despite encouraging initial results candidate peptides could not be functionally validated as ubiquitin-binding through protein NMR spectroscopy. Finally, biochemical approaches with ubiquitin-affinity chromatography, LC-MS/MS identification and validation by protein NMR were used to uncover previously unidentified ubiquitin-binding proteins. This multi-discipline approach led to the identification of a novel ubiquitin-binding protein, peflin. This protein did not contain any known UBD, suggesting the presence of a candidate novel UBD. As peflin is a calcium-binding penta-EF hand protein the effect of calcium on the peflin-ubiquitin interaction was investigated. Initial results indicated that calcium potentiated the interaction, providing evidence for the first known example of calcium and ubiquitin signal integration within a ubiquitin-recognition protein. Unexpectedly, ubiquitin was also found to respond to physiologically relevant calcium concentrations in the absence of any protein ligand. It was speculated that this could act to tailor ubiquitin signals in high calcium cell compartments for signal localisation. This preliminary data can be contextualised with recent reports of alternative ubiquitin conformational states and previous instances of ubiquitin binding to other divalent metal cations. Taken together, the concepts discussed here work towards the identification of new UBDs which may represent the ‘dark matter’ of the ubiquitin system.